The role of molluscs in monitoring marine pollution and its connection to climate change and ESG - Yap, Chee Kong; Aguol, Kennedy Aaron; Ong, Meng Chuan; Wan Mohd Syazwan; Nulit, Rosimah; Okamura, Hideo; Horie, Yoshifumi; Ismail, Mohamad Saupi; Setyawan, Ahmad Dwi; Kumar, Krishnan; Cheng, Wan Hee; Leow, Chee Seng (Enviro Research Publishers, 2024)
Molluscs possess a unique capability to filter and remove pollutants from water, offering a natural and effective solution to combat marine pollution. Their filtration process not only enhances water quality but also mitigates the detrimental impacts of contaminants on marine ecosystems. As climate change introduces unprecedented challenges, the resilience of molluscs—particularly in adapting to rising temperatures and ocean acidification—highlights their critical role in sustaining marine ecosystem balance. This paper reviews the literature on molluscs from 1874 to 2024, as documented in the Scopus database, analyzing 5,757 publications retrieved on 8 March 2024. Five major insights emerged: (a) molluscs’ significant ecological role, (b) the potential of marine bivalves for ecosystem health and sustainability, (c) the importance of monitoring molluscs to address climate change, (d) the scarcity of studies linking molluscs to Environmental, Social, and Governance (ESG) practices, and (e) existing knowledge gaps. Understanding and monitoring mollusc populations are essential for advancing environmental stewardship, fostering social responsibility, and promoting sound governance. Integrating these aspects within business operations can support marine ecosystem resilience and reflect a commitment to the planet's and society's holistic well-being.